Development of the Global Mycetoma Working Group. (15th December 2020) - Traxler, Rita M; Beer, Karlyn D; Blaney, David D; van de Sande, Wendy W J; Fahal, Ahmed H; Asiedu, Kingsley B; Bower, William A; Chiller, Tom
Abstract: The Global Mycetoma Working Group (GMWG) was formed in January 2018 in response to the declaration of mycetoma as a neglected tropical disease (NTD) by the World Health Assembly. The aim of the working group is to connect experts and public health practitioners around the world to accelerate mycetoma prevention activities and reduce the impact of mycetoma on patients, healthcare providers and society in the endemic regions. The working group has made tangible contributions to mycetoma programming, awareness and coordination among scientists, clinicians and public health professionals. The group's connectivity has enabled rapid response and review of NTD documents in development, has created a network of public health professionals to provide regional mycetoma expertise and has enabled mycetoma to be represented within broader NTD organizations. The GMWG will continue to serve as a hub for networking and building collaborations for the advancement of mycetoma clinical management and treatment, research and public health programming.